LGG-06. COMPREHENSIVE GENOMIC CHARACTERIZATION AND INTEGRATED CLINICAL ANALYSIS OF LOW-GRADE GLIOMAS IN CHILDREN WITH NEUROFIBROMATOSIS TYPE 1. (1st June 2021) - Fisher, Michael; Jones, David; Li, Yimei; Guo, Xiaofan; Sonawane, Poonam; Waanders, Angela; Phillips, Joanna; Weiss, William; Resnick, Adam; Gosline, Sara; Banerjee, Jineta; Guinney, Justin; et al.
Abstract: Background: Low-grade gliomas (LGGs) arising in children with neurofibromatosis type 1 (NF1) are usually not biopsied. To identify secondary genetic alterations or molecular features that may contribute to pathogenesis and correlate with clinical behavior, we initiated a comprehensive molecular and clinical analysis of pediatric NF1-LGGs. Methods: NF1-LGGs were analysed by whole-genome sequencing (31), targeted gene panel sequencing (9), RNAseq transcriptomal profiling (33) and genome-wide DNA methylation analysis (67). Clinical annotation was available for 48 subjects. Results: Most LGGs harbored bi-allelic NF1 inactivation as the sole genetic abnormality, but 11% had additional alterations ( FGFR1 mutation, n=3; PIK3CA mutation, n=2; homozygous 9p21 deletion, n=2; MYB:QKI fusion, n=1; SETD2 mutation, n=1; EGFR amplification, n=1). FGFR1 mutation conferred additional growth advantage in multiple complementary murine Nf1 models. 88% of NF1-LGGs resembled sporadic pilocytic astrocytoma (PA) by methylation, higher than that based on histology. Non-PA methylation patterns included low-grade glial/glioneuronal tumors, rosette-forming glioneuronal tumors, MYB/MYBL1-altered glioma, and high-grade astrocytoma with piloid features (2 tumors histologically diagnosed as LGG). In total, 18% of samples were classified as non-PA and/or harbored an additional non- NF1 mutation. Non-PA methylation class tumors were more likely to harbor an additional non- NF1 mutation (p=0.005). 7.7% of optic pathway hypothalamic gliomas (OPHGs) had other mutations or were not classified by methylation as PA, compared with 20.6% of NF1-LGGs arising elsewhere. There was no difference based on age for the presence of an additional non- NF1 mutation or non-PA methylation class. Conclusions: Given the overall low occurrence of non- NF1 mutations or non-PA methylation class tumors in this series, routine clinical biopsy of typically-appearing NF1-LGG may not be indicated, particularly for children with OPHG. Biopsy should be considered for non-OPHG tumors refractory to conventional treatment. As additional agents are developed and treatment strategies evolve, the rationale for biopsy of NF1-LGG may become stronger.